Galerie Wanda Reiff Maastricht : Tentoonstellingen 1985-1987. - Galerie Wanda Reiff, Maastricht (Maastricht : Galerie Wanda Reiff, 1988)
Oehlen, Albert ; Büttner, Werner ; Bömmels, Peter ; Raveel, Roger ; Kippenberger, Martin ; Slits, Ton ; Knap, Jan ; Claessen, Wim ; Defesche, Peter ; Dahn, Walter ; Wehrens, Peter ; Droese, Felix ; Baselitz, Georg ; Buthe, Michael ; Garouste, Gérard ; Paladino, Mimmo ; Vugs, Joop ; Wolff, Carl Emanuel ; De Maria, Nicola
Nederlands & Engels
boek